Strategi Manajemen Risiko dan Keamanan Siber dalam Ekonomi Digital: Tinjauan Literatur - Asiyanti, Adinda Priski Dhea; Agussalim Agussalim (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research discusses the significant role of digital technology in the modern economy, particularly in relation to cybersecurity and the impact of technological disruption on business sustainability. The main topics analyzed include the use of artificial intelligence (AI) to detect cyber threats, strategies for protecting IT supply chains, and the challenges faced by the banking sector and the Internet of Things (IoT) in managing cybersecurity risks. The research also examines the impact of digitalization on social inequality and poverty in the European Union. Digital technologies such as automation, data analytics, and IoT drive innovation and enhance operational efficiency, but also introduce disruptive challenges that must be addressed through careful risk management and increased organizational capacity to ensure business resilience.